The Effect of Snowball Throwing Cooperative Learning Assisted by PhET Simulation on Students' Physics Learning Outcomes and Responses on Heat Material - Mashitoh, Nidya Nur; Indrawati, Indrawati; Nuraini, Lailatul (Universitas Lambung Mangkurat, 2024)
In an effort to increase student involvement and maintain the diversity of models in the teaching and learning process, a variety of learning models are needed. The combination of a snowball throwing model assisted by PhET simulation can provide a more interactive and in-depth learning experience for students. The purpose of this research is twofold: first, to examine the effect of the snowball-throwing cooperative model assisted by PhET on learning outcomes and learning responses of physics students in high school. This research used pseudo-experimental research, known as a pseudo-experiment with a quantitative approach. The population in this study was SMAN Rambipuji. The sample used was grade 11 students. Sampling in the study used cluster random sampling and homogeneity testing, constituting the research sample as an experimental class and a control class. This research shows a significant increase, namely in the value of Asymp. Sig. (2-tailed) 0.000 < 0.05 on the physics learning outcomes of high school students who use the cooperative snowball throwing model assisted by PhET simulation. Apart from that, there was a significant difference between the cognitive, affective and conative dimension scores of the experimental group students compared to the control group. This shows that students have a better understanding of the material, high learning motivation, and the ability to actively ask and respond to questions when using the snowball-throwing cooperative model assisted by PheT simulations on learning outcomes and responses to physics learning.